Emigración, movilización militar y cultura de guerra. Los franceses de la Argentina durante la Gran Guerra - Hernán Otero (Amnis)
World War I brought about a significant redefinition of the role played by European emigrant communities overseas. Through an analysis of military and diplomatic archives (Service Historique de l’Armée de Terre, Ministère des Affaires Étrangères de Paris, Centre des Archives Diplomatiques de Nantes), this paper studies the response of French residents in Argentina to the military mobilization by their motherland for World War I. This response is seen as an extreme case of the social tensions that emerged from the bonds –both legal and cultural– that tied emigrants both to their homeland and their newly adopted land of residence. With this purpose, this work analyzes the degree of success of the call to arms among French residents in Argentina. A comparison of the results with those of other belligerent communities –Italians, English – allows an exploratory explanation of their attitude, based on cultural elements –such as the influence of nationalism–, on institutional aspects –the impact of military policies–, personal dimensions – sense of belonging to a community– and sociological elements, such as the degree of integration into the local society. Finally, a comparison between the French residing in Europe and those dwelling in Argentina is the basis for a consideration of the concept of “war culture”, which emphasizes the advantages of considering the plurality of its configurations, and of not overlooking the coercive elements that intervened in the war mobilization.